Comparison of antifungal and cytotoxicity activities of titanium dioxide and zinc oxide nanoparticles with amphotericin B against different Candida species: In vitro evaluation. Issue 1 (12th September 2020) - Ahmadpour Kermani, Shima; Salari, Samira; Ghasemi Nejad Almani, Pooya
Abstract: Background: Candida species are known to cause serious fungal infections that produce cutaneous, mucosal, and systemic infections. Nowadays, mortality and morbidity candidiasis in immunocompromised patients have increased. Nanotechnology is a new world‐known technology and includes particles ranging from about 1 to 100 nanometers. The purpose of this study was to evaluate the antifungal and cytotoxicity activities of titanium dioxide nanoparticles (TiO2‐NPs) and zinc oxide nanoparticles (ZnO‐NPs) compared to amphotericin B (AmB) on different Candida spp in in vitro conditions. Methods: In the present study, susceptibility of different Candida species to TiO2‐NPs and ZnO‐NPs compared to AmB was determined by broth microdilution (BMD) and agar well diffusion methods. Cytotoxicity of TiO2‐NPs and ZnO‐NPs and amphotericin B was measured by MTT (3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐Diphenyltetrazolium Bromide) assay. Results: The results indicated that the TiO2‐NPs and ZnO‐NPs showed antifungal activities against pathogenic Candida spp. The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of TiO2‐NP ranges against Candida spp. were 128‐256 µg/mL and 256‐512 µg/mL, respectively. The MIC and MFC values of ZnO‐NPs were 64‐128 µg/mL and 256‐512 µg/mL, respectively. However, MICs and MFCs of AmB were 8‐16 µg/mL and 16‐32 µg/mL, respectively. The MTT assay results showed that the CC50% belonged to ZnO‐NPs 706.2 μg/mL, for TiO2‐NPs 862.1 μg/mL, and for AmB 70.19 μg/mL, respectively. Conclusion: Our findings showed that TiO2‐NPs and ZnO‐NPs had antifungal effects against all Candida species, yet the antifungal properties of TiO2‐NPs and ZnO‐NPs were significantly less than those of AmB. The CC50% of AmB was significantly lower than ZnO‐NPs and TiO2‐NPs. Abstract : In the present study, susceptibility of different Candida species to TiO2‐NPs and ZnO‐NPs compared to AmB was determined by broth microdilution (BMD) and agar well diffusion methods. Cytotoxicity of TiO2‐NPs and ZnO‐NPs and amphotericin B was measured by MTT (3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐Diphenyltetrazolium Bromide) assay. The results indicated that the TiO2‐NPs and ZnO‐NPs showed antifungal activities against pathogenic Candida spp. The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of TiO2‐NPs ranges against Candida spp. were 128‐256 µg/mL and 256‐512 µg/mL, respectively. The MIC and MFC values of ZnO‐NPs were 64‐128 µg/mL and 256‐512 µg/mL, respectively. MICs and MFCs of AmB were 8‐16 µg/mL and 16‐32 µg/mL, respectively. The MTT assay results showed that the CC50% belonged to ZnO‐NPs 706.2 μg/mL, for TiO2‐NPs 862.1 μg/mL, and for AmB 70.19 μg/mL, respectively.